Synthesis and Properties of Novel Polyethylene‐Based Antioxidants with Hindered Phenols as Side Groups. Issue 3 (18th December 2019) - Zhang, Yin; Li, Huayi; Li, Mengru; Liu, Weiwei; Li, Qian; Hu, Youliang
Abstract: Novel polyethylene‐based (PE‐based) antioxidants derived from commercially available ethylene‐vinyl acetate copolymer (EVA) with PE as the backbone and hindered phenols as side groups are prepared, and their potential for application as non‐migrating polyolefin stabilizers is investigated. The synthesis route contains the typical hydrolysis of EVA and transesterification reaction between the hydrolysis product and methyl 3‐(3, 5‐di‐tert‐butyl‐4‐hydroxyphenyl) propionate. Thermal stabilities of these PE‐based antioxidants (AO‐PE) are studied through thermal analysis under an air atmosphere and shown to be higher than those of antioxidant 1076 and antioxidant 1010 (AO‐1010) due to their macromolecular structures. Antioxidant activities of the AO‐PE are evaluated in polypropylene (PP) by measuring the melt flow index of multiple‐extruded stabilized PP, and the results demonstrate that the antioxidant effectiveness of these antioxidants is strongly related to the molecular weight. Abstract : Novel polyethylene‐based antioxidants are prepared via a transesterification reaction based on hydroxylated polyethylene obtained by hydrolysis of acetate copolymer. Their antioxidant activities are evaluated in polypropylene (PP) by measuring the melt flow index of multiple‐extruded stabilized PP. As macromolecular antioxidants with polyethylene as backbone, the polyethylene‐based antioxidants are expected to exhibit the advantages of volatilization resistance, migration resistance, and good compatibility with polyolefins.